Slappy Birthday to You : Goosebumps SlappyWorld #1 - Stine, R. L. (New York, NY : Scholastic Inc., 2017)
"It's bad enough Ian Barker has to spend his twelfth birthday with his sister and their two annoying cousins. The four of them can't ever hang out without getting into trouble. Vinnie and Jonny always want to play with Ian's stuff. They take extra turns and break everything they touch. Even Ian's new birthday presents are up for grabs. But when Ian gets a Slappy dummy from his dad, things go from bad to worse. When Slappy's in charge, you don't fight over him, he fights over you!"--Page [4] of cover.
Contains excerpt of the next Goosebumps Slappyworld series.
Appeals to 4th-6th graders.
Reading level grade 4.
Keywords: Brothers and sisters -- Juvenile fiction; Cousins -- Juvenile fiction; Birthdays -- Juvenile fiction; Ventriloquists' dummies -- Juvenile fiction; Ventriloquists' dummies -- Fiction; Birthdays -- Fiction; Horror stories; JUVENILE FICTION / Horror; JUVENILE FICTION / Humorous Stories; Birthdays; Brothers and sisters; Cousins; Ventriloquists' dummies; Fiction; Juvenile works; Horror fiction; Horror fiction